Faith as a religious outlook - Olena I. Predko (Українське Pелігієзнавство, 2005)
One of the pressing problems of modern society is the problem of finding spiritual landmarks, which creates an urgent need to form a new paradigm of worldview. After all, a person, being in self-knowledge and self-creation, seeks more and more opportunities to realize their essential forces, seeks to fulfill their vital purpose and thereby to carry out the process of self-affirmation and self-fulfillment. In this action, all the essential forces of man and, in particular, his phenomenon as a religious belief are involved, by which man not only experiences his YAH, but also seeks to go beyond it.